أهداف تدريس العلوم الطبيعية في مراحل التعليم العام من منظور إسلامي: Aims of Science Education from an Islamic Perspective - Al-Hidabi, Dawood Abdulmalek Yahya; Aljaji, Raja (IIUM Journal of Educational Studies, 2020)
The fundamental purpose of the study is to establish what should be the primary aims of science education from an Islamic perspective via a content analysis. The qualitative method of content analysis was adopted to derive the aims where a total of 4 types of texts of different sources were analyzed namely Quranic verses related to natural phenomena, Islamic Maqasid, acquired human knowledge in science education, and the current situations/contexts and needs of society. A researcher-developed thematization process consisting of 20 categories was followed to guide the analysis process. The process resulted in fifty-nine (59) aims being derived from the four categories of Islamic resources, subsequently classified into twenty dimensions. The aims and dimensions include Aqeda, thinking, scientific applications, integration, and scientific literacy. Based on the research results, the study recommends that the science curricula of Muslim schools be restructured along the extracted aims so that the science education imparted to Muslim students is more in line with Islamic teachings and Islamic world view.